2017
DOI: 10.1530/rep-17-0396
|View full text |Cite
|
Sign up to set email alerts
|

Altered miRNA-profile dependent on ART outcome in early pregnancy targets Wnt-pathway

Abstract: Main goal of this study is to detect the possible alterations in microRNA (miRNA) expression and the pathway targeted in plasma at the time of embryo transfer and pregnancy testing dependent on the assisted reproductive treatment (ART) outcome after ovarian hyperstimulation for fertilization. Changes in miRNA expression in plasma of women, who became pregnant ( = 6) vs women who failed implantation ( = 6) following day 5 embryo transfer (ET), were investigated at the day of ET and pregnancy testing (PT). Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Since the discovery of dmrt1bY in the Japanese rice fish [28,29], the first identified teleost master sex determination gene, studies in teleosts have unveiled a dozen novel genes as master regulators for sex determination [1416,27]. Interestingly, many of these master sex determining genes belong to the TGF- β superfamily.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of dmrt1bY in the Japanese rice fish [28,29], the first identified teleost master sex determination gene, studies in teleosts have unveiled a dozen novel genes as master regulators for sex determination [1416,27]. Interestingly, many of these master sex determining genes belong to the TGF- β superfamily.…”
Section: Discussionmentioning
confidence: 99%
“…Beside this remarkable dynamic of sex determination systems, the rapid turnover of sex chromosomes in teleosts provides many opportunities to examine sex chromosome pairs at different stages of differentiation. Finally, recent studies on fish sex determination have revealed a dozen new master sex determining (MSD) genes [14,16,27], providing additional insight to the forces driving the turnover of SD systems and the formation of sex chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Beta‐catenin and Wnt7a mRNAs are upregulated and Wnt3 is downregulated in the transition from the proestrus to the estrus stage, and the opposite relationship occurs when switching from metaestrus to diestrus, suggesting that transition stages to estrus and diestrus may be decisive for the Wnt signaling pathway. Although the precise mechanism involving the Wnt7a and Wnt3 regulation remains unclear, it may be responsive to steroid hormones (Rider et al, 2006, 2016) and microRNAs (miRNAs) since the 11 miRNAs showing the highest significant alterations were all associated with the regulation of Wnt3 and Wnt7a (Freis et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…showing the highest significant alterations were all associated with the regulation of Wnt3 and Wnt7a (Freis et al, 2017).…”
mentioning
confidence: 99%
“…In this review, we reviewed work analyzing the potential of miRNA isolated from blastocyst and endometrium in predicting the window of implantation or likelihood of successful implantation. Freis et al explored microRNA in serum during the window of implantation and found four miRNAs that could be possible biomarkers for implantation success [57]. However, studies profiling miRNA expression show inconsistent results due to the complexity of miRNA signaling, its rapid variation with time, and variation between individuals.…”
Section: Conclusion and Future Implicationsmentioning
confidence: 99%